2021
DOI: 10.1101/2021.04.09.439219
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

TBX5 drivesAldh1a2expression to regulate a RA-Hedgehog-Wnt gene regulatory network coordinating cardiopulmonary development

Abstract: The gene regulatory networks that coordinate the development of the cardiac and pulmonary systems are essential for terrestrial life but poorly understood. The T-box transcription factor Tbx5 is critical for both pulmonary specification and heart development, but how these activities are mechanistically integrated remains unclear. We show that Tbx5 regulates an evolutionarily conserved retinoic acid (RA)-Hedgehog-Wnt signaling cascade coordinating cardiopulmonary development. We demonstrate that Tbx5 directly … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 80 publications
(94 reference statements)
0
2
0
Order By: Relevance
“…During embryonic development, Raldh2 is co-expressed with Tbx5 in a subset of pSHF progenitors (Hochgreb et al, 2003;Ryckebusch et al, 2008;De Bono et al, 2018), and Raldh2 knockouts display reduced Tbx5 expression (Niederreither et al, 2001;Sirbu et al, 2008). Furthermore, a recent study revealed that Tbx5 promotes pSHF identity through a positive feedback loop with Raldh2 (Rankin et al, 2021). Importantly, Tbx5 regulates the expression of a key pacemaker gene, Shox2…”
Section: Stem Cell Reportsmentioning
confidence: 99%
See 1 more Smart Citation
“…During embryonic development, Raldh2 is co-expressed with Tbx5 in a subset of pSHF progenitors (Hochgreb et al, 2003;Ryckebusch et al, 2008;De Bono et al, 2018), and Raldh2 knockouts display reduced Tbx5 expression (Niederreither et al, 2001;Sirbu et al, 2008). Furthermore, a recent study revealed that Tbx5 promotes pSHF identity through a positive feedback loop with Raldh2 (Rankin et al, 2021). Importantly, Tbx5 regulates the expression of a key pacemaker gene, Shox2…”
Section: Stem Cell Reportsmentioning
confidence: 99%
“…Interestingly, both in limb and lung development, where Tbx5 plays an important role, the transcription factor interacts with canonical WNT signaling. Whereas in limb development canonical WNT signaling is upstream of Tbx5, in lung development Tbx5 activates the expression of Wnt2 in cardiopulmonary progenitors (Ng et al, 2002;Nishimoto et al, 2015;Steimle et al, 2018;Rankin et al, 2021). WNT signaling has also been identified as a critical cue for pacemaker development (Bressan et al, 2013;Ren et al, 2019).…”
Section: Stem Cell Reportsmentioning
confidence: 99%